2023
DOI: 10.3390/brainsci13010094
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Geriatric Traumatic Brain Injury Patients Using Machine Learning Algorithms

Abstract: Background: The number of geriatric traumatic brain injury (TBI) patients is increasing every year due to the population’s aging in most of the developed countries. Unfortunately, there is no widely recognized tool for specifically evaluating the prognosis of geriatric TBI patients. We designed this study to compare the prognostic value of different machine learning algorithm-based predictive models for geriatric TBI. Methods: TBI patients aged ≥65 from the Medical Information Mart for Intensive Care-III (MIMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Similar to the present study, the random forest algorithm showed the best performance, and Logistic Regression yielded acceptable results. In a study by Wang et al [23], it was reported that prognostication tools utilizing Adaboost, Random Forest, and Logistic Regression algorithms proved beneficial for physicians in assessing the risk of poor outcomes in geriatric patients with TBI and in guiding the selection of personalized therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the present study, the random forest algorithm showed the best performance, and Logistic Regression yielded acceptable results. In a study by Wang et al [23], it was reported that prognostication tools utilizing Adaboost, Random Forest, and Logistic Regression algorithms proved beneficial for physicians in assessing the risk of poor outcomes in geriatric patients with TBI and in guiding the selection of personalized therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Fen et al compared the predictive abilities of twentytwo machine learning models with a logistic regression model, using performance measures such as ROC, AUC, accuracy, F-score, precision, recall, and decision curve analysis [22]. Another research focused on evaluating diagnostic accuracy for traumatic brain injury in elderly patients using various machine learning algorithms [23]. Rau et al predicted patient deaths using logistic regression, support vector machine, decision tree, naive Bayes, and artificial neural network models [24].…”
mentioning
confidence: 99%
“…While these tools provide valuable information, on their own they struggle to capture the complexity of the multifaceted nature of TBI, which limits their prognostic ability in terms of accuracy and individualized risk assessment [ 15 ]. This has prompted researchers and clinicians to explore alternative approaches that leverage the power of machine learning algorithms to improve predictive models in the field of TBI [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%